Analisis Kepatuhan Masyarakat Membayar Pajak Bumi dan Bangunan (PBB) di Kota Palembang - Endang Kusdiah Ningsih; Dwi Eka Novianty; Esty Naruliza (Universitas Indo Global Mandiri)
One of taxes which was potentially to be explored as revenue source is Land and building tax. However, the realization of land and building tax revenue has always been below the target. The main purpose of this research is to analyze public compliance in paying land and building tax. This research was conducted with a survey method with a population of 9.174 and a study sample of 369 taxpayers. Data collection techniques used were in the form of questionnaires distributed to land and building taxpayers in three district in Palembang.The results of this study, Thefisrt factor that underlies compliance with paying land and building taxes is administrative requirements (78,59%), furthermore, the factors of tax sanctions, economy and awareness of paying taxes each of 11,38%, 5,96% and 4,07%.Keywords: Land and Building Tax , Tax Compliance